Haematological and immunological plasma assays and histological study of the grass carp (Ctenopharyngodon idella) to determine health status. (9th June 2020) - Li, Lisen; Wang, Shentong; Shen, Yubang; Xu, Xiaoyan; Dang, Yunfei; Zhang, Meng; Huang, Wenji; Li, Jiale
Abstract: To investigate the health status of farmed Ctenopharyngodon idella, haematology, serum biochemistry, and histology analyses were carried out. Growth performance measurement shows Fulton's condition factor is 1.69. The hepatic somatic index (0.42 ± 0.09) was markedly lower than the reference values (1.2–2.55 ± 0.24). The white blood cell counts (1.57 × 10 8  ± 0.37 × 10 7 cell/ml) were approximately 10 times higher than reference values (0.2974 ± 0.00315) × 10 7  – (1.457 ± 0.69) × 10 7 cell/ml, as was mean corpuscular volume. The percentage of neutrophil (5.29%) was lower than the reference values (11.59%–39.97%), but thrombocyte proportion (32.32%) was higher than the reference (4.31 ± 7.7%). Activities of plasma alanine transaminase (2.38 ± 1.10 U/L) and aspartate aminotransferase (3.72 ± 1.25 U/L) were lower than reference values (ALT: 4.96–15.84 U/L; AST: 40.66–116.47 U/L). Combined, all reference value of complement C3 content indicates a negative correlation with body size, but C4 and immunoglobulin M was positively correlated. Peroxidase activity was 500 times higher than the reference, possibly due to fish size. Histological diagnosis showed that the Organ indexes (OI) of gill (12.0 ± 8.9) and liver (11.9 ± 12.9) were higher than kidney (7.1 ± 5.5) and intestine (5.0 ± 5.5). Moderate and pronounced histological differences were observed in gills and livers, but the kidney and intestine were mostly normal. This preliminary study has found the difference of health in farmed grass carp and try to reflect the potential health status of farmed fish.